Monitoring for invasive and endemic mosquitoes at UK ports. Issue 29 (2011) - Vaux, Alexander G.C.; Murphy, Gai; Baskerville, Nick; Burden, Ged; Convery, Niall; Crossley, Lynnette; Dettman, Laurence; Haden, Paul; Jarrold, Laurence; Massey, Christopher; Napier, Kevin; Pocknell, Iain; et al.
No abstract available